A new high-temperature superconducting double-hybrid coupler with wide bandwidth - Bechteler, Thomas; Mayer, Bernd; Weigel, Robert (Microwave Symposium Digest, IEEE MTT-S International, 1997)
We report on the design and performance of new high-temperature superconducting couplers fabricated in microstrip technology. We present experimental results for a 3 dB- and a 0 dB-coupler (i.e. a crossover device) at 10 GHz. The planar coupler structures were patterned into YBaCuO thin films deposited on MgO substrates on both sides. As a design tool, we employed a commercial microwave simulation program. Verification was done using special test chips. We attained extremely low insertion loss values over bandwidths of 45 per cent (3 dB-coupler) and 30 per cent (0 dB-coupler), respectively.
elib2cris::1512001600,bechteler1997a
Keywords: Bandwith; Circuit simulation; circuit testing; couplings; Couplings; High temperature superconductors; microstrip; Superconducting microwave devices; Superconducting transmission lines; Transmission line theory; Yttrium barium copper oxide